Oxidation of Paracetamol Drug by a New Oxidant Diperiodatoargentate (III) in Aqueous Alkaline Medium - D. C. Hiremath; C. V. Hiremath; S. T. Nandibewoor (E-Journal of Chemistry)
The kinetics of oxidation of anti-pyretic drug, paracetamol by diperiodatoargentate (III) (DPA) in alkaline medium at a constant ionic strength of 0.01 mol dm-3 was studied spectrophotometrically. The reaction between DPA and paracetamol in alkaline medium exhibits 1:2 stoichiometry (paracetamol: DPA). The reaction is of first order in [DPA] and has less than unit order in both [PAM] and [alkali]. A decrease in the dielectric constant of the medium increases the rate of the reaction. The effect of added products and ionic strength of the reaction medium have been investigated. The oxidation reaction in alkaline medium has been shown to proceed via a DPA- paracetamol complex, which decomposes slowly in a rate determining step followed by other fast step to give the products. The main products were identified by spot test, IR, NMR and GC-MS. The reaction constants involved in the different steps of the mechanism are calculated. The activation parameters with respect to slow step of the mechanism are computed and discussed and thermodynamic quantities are also determined.